Systemic Inflammatory Cytokines Predict the Infectious Complications but Not Prolonged Postoperative Ileus after Colorectal Surgery - G. S. A. Boersema; Z. Wu; A. G. Menon; G. J. Kleinrensink; J. Jeekel; J. F. Lange (Hindawi Limited, 2018)
Aim. Postoperative ileus (POI) is common after surgery. Animal studies indicate that the POI mechanism involves an inflammatory response, which is also activated during postoperative complications. This study aimed to determine whether inflammatory biomarkers might facilitate an early detection of prolonged POI (PPOI) or infectious complications. Methods. Forty-seven adult patients who underwent oncological colorectal surgery were included. They filled out a perioperative diary to report their gastrointestinal symptoms. Blood samples were collected preoperatively, and on postoperative day (POD) 1 and 3. Levels of leucocytes, C-reactive protein (CRP), interleukin (IL)-6, TNF-α, and IL-1β were analyzed. Results. Patients with PPOI had significantly longer stay in hospital than patients without (13.6 ± 10.5 versus 7.4 ± 3.2 days, p<0.001); they also had higher levels of IL-6 ratios, leucocytes, and CRP levels, but did not reach significance. Higher levels of postoperative IL-6 and CRP levels (p<0.05, resp.) were found in patients with infectious complications. The receiver operating characteristic (ROC) analysis found better diagnostic values of IL-6 ratio on both POD 1 and 3 than that of CRP (POD 1: ROC 0.825, p<0.001). Conclusion. Blood levels of inflammatory cytokines cannot predict PPOI after colorectal surgery. Instead, postoperative IL-6 changes may predict the infectious complications with a better diagnostic value than the current leukocytes or CRP tests.